Respostas
respondido por:
0
Bom dia
- 3x - 16 = - 2(3x - 7)
- 3x - 16 = - 6x + 14
- 3x + 6x = 14 + 16
3x = 30
x = 30 / 3
x = 10
- 3x - 16 = - 2(3x - 7)
- 3x - 16 = - 6x + 14
- 3x + 6x = 14 + 16
3x = 30
x = 30 / 3
x = 10
respondido por:
0
Olá!
-3x - 16 = -2.(3x - 7)
-3x - 16 = -6x + 14
-3x + 6x = 14 + 16
3x = 30
x = 30/3
x = 10
-3x - 16 = -2.(3x - 7)
-3x - 16 = -6x + 14
-3x + 6x = 14 + 16
3x = 30
x = 30/3
x = 10
Perguntas similares
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás